High-current resolution broad-band SQUID amplifier suitable for TES calorimeter. - Morooka, T. (IEEE Transactions on applied superconductivity)
A superconducting quantum interference device (SQUID) amplifier has been developed as a current detector with both high-current resolution and broad bandwidth for a transition edge sensor calorimeter. The amplifier is a two stage SQUID (TSS) that consists of an input-SQUID with a 38-turn input coil and a 100-serial SQUID array (100-SSA) output, and has been integrated on a 3 × 3 mm Si chip using Nb thin film fabrication technology. It is designed to increase the amplifier gain and maintain matching with the parameters of the calorimeter. To avoid flux trapping in the SSA, the washer coil of the dc-SQUIDs in the SSA was made with a narrow line width of 17.5 μm. We experimentally confirmed that the designed output voltage was achieved using a one-layer p-metal magnetic shield tube in the earth's magnetic field. The performance of the shielded TSS amplifier was evaluated in liquid helium. The TSS amplifier had a gain of 10 kV/A and an impedance of 0.07 Ω at 100 kHz. When a flux locked loop circuit was used to drive the amplifier, a current resolution of 1 pA/√Hz and a rise time of 1 μs were achieved